Construction and validation of indicators for patient safety in intrahospital transport - Endric Passos Matos; Deybson Borba de Almeida; Kátia Santana Freitas; Silvone Santa Bárbara da Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To construct and validate an indicator plan for measuring and assessing patient safety in intrahospital transport. Method: Methodological study, developed in three stages, between July 2018 and July 2019. The content validity included the participation of nurses from the State of Bahia and experts from different regions of the country. For data analysis and interpretation, descriptive statistics were used. Results: After a pre-test round and two rounds of expert consultations, using the Delphi technique, the general content validity index that assessed the clarity of the indicators was measured at 1.00 and the representativeness was 0.97. Conclusion: The indicators make a significant contribution to the field of health and nursing, as it constitutes an instrument that will contribute to the professional practice of nurses, to patient safety and will still be viable for the practice of auditing or assessing the intrahospital transport process.